Systematic review and meta-analysis of the relationship between EPHX1 polymorphisms and colorectal cancer risk. - Fei Liu; Ding Yuan; Yonggang Wei; Wentao Wang; Lvnan Yan; Tianfu Wen; Mingqing Xu; Jiayin Yang; Bo Li (PLoS ONE, 2012)
Background Microsomal epoxide hydrolase (EPHX1) plays an important role in both the activation and detoxification of PAHs, which are carcinogens found in cooked meat and tobacco smoking. Polymorphisms at exons 3 and 4 of the EPHX1 gene have been reported to be associated with variations in EPHX1 activity. The aim of this study is to quantitatively summarize the relationship between EPHX1 polymorphisms and colorectal cancer (CRC) risk. Methods Two investigators independently searched the Medline, Embase, CNKI, and Chinese Biomedicine Databases for studies published before June 2012. Summary odds ratios (ORs) and 95% confidence intervals (CIs) for EPHX1 Tyr113His (rs1051740) and His139Arg (rs2234922) polymorphisms and CRC were calculated in a fixed-effects model and a random-effects model when appropriate. Results This meta-analysis yielded 14 case-control studies, which included 13 studies for Tyr113His (6395 cases and 7893 controls) and 13 studies for His139Arg polymorphisms (5375 cases and 6962 controls). Overall, the pooled results indicated that EPHX1 Tyr113His polymorphism was not associated with CRC risk; while the His139Arg polymorphism was significantly associated with decreased CRC risk (Arg/His vs. His/His, OR = 0.90, 95%CI = 0.83-0.98; dominant model, OR = 0.92, 95%CI = 0.85-0.99). The statistically significant association between EPHX1 His139Arg polymorphism and CRC was observed among Caucasians and population-based case-control studies. This association showed little heterogeneity and remained consistently strong when analyses were limited to studies in which genotype frequencies were in Hardy-Weinberg equilibrium, or limited to studies with matched controls. When cumulative meta-analyses of the two associations were conducted by studies' publication time, the results were persistent and robust. Conclusion This meta-analysis suggests that EPHX1 Tyr113His polymorphism may be not associated with CRC development; while the EPHX1 His139Arg polymorphism may have a potential protective effect on CRC.